2023
DOI: 10.1158/0008-5472.can-22-3014
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Value of Circular Noncoding RNA Research in Cancer Diagnosis and Treatment

Abstract: Circular RNAs (circRNA) are a recently described class of RNA molecules that have attracted substantial attention as new components of disease mechanisms and as potential biomarkers in multiple diseases, including cancer. CircRNAs are often highly conserved and exhibit developmental stage- and disease-specific expression. Several studies have reported circRNA expression patterns that are associated with specific cancer types and with patient prognosis. Here, we overview the active registered clinical trials th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These diverse functions of circRNAs provide a new perspective on the complexity of gene regulation in cancer 34 . the unique characteristics and diverse functions of circRNAs, as well as their dysregulated expression in cancer, have made them a hot topic in cancer research 35 . Although circRNA has been implicated in prostate cancer, its molecular mechanism and biological role have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…These diverse functions of circRNAs provide a new perspective on the complexity of gene regulation in cancer 34 . the unique characteristics and diverse functions of circRNAs, as well as their dysregulated expression in cancer, have made them a hot topic in cancer research 35 . Although circRNA has been implicated in prostate cancer, its molecular mechanism and biological role have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma patients with high circ-SORE had poor recurrence-free survival, and its tissues content was proposed as a good predictor of sorafenib efficacy [ 38 ]. Also, circular RNA is demonstrated to be enriched and stable in human peripheral blood [ 39 , 40 ]. F-circEA [ 41 ], circ-CCAC1 [ 42 ], circ-N4BP2L2 [ 43 ] and circ-RNF220 [ 44 ] were abundantly expressed in human peripheral blood, which could be used as the biomarkers for diagnosis of EML4-ALK -positive non-small cell lung cancer, cholangiocarcinoma, epithelial ovarian cancer and pediatric acute myeloid leukemia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the identification of endogenous circRNAs and the elucidation of their functions, circRNA sponging miRNAs to alleviate the degradation or translation repression of target mRNAs has been increasingly described, especially in processes related to oncology. 331 , 332 It is worth mentioning that the establishment of engineered circRNAs to mimic endogenous or exosomal noncoding circRNAs, which enables the manipulation of ceRNA interactions, may engender new research fields or disease therapeutic schedules. More broadly, many translatable natural endogenous circRNAs have been identified that have important roles in disease occurrence and progression.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%